Near-infrared emitting graphene quantum dots synthesized from reduced graphene oxide for in vitro/in vivo/ex vivo bioimaging applications. (6th April 2021) - Hasan, Md Tanvir; Lee, Bong Han; Lin, Ching-Wei; McDonald-Boyer, Ainsley; Gonzalez-Rodriguez, Roberto; Vasireddy, Satvik; Tsedev, Uyanga; Coffer, Jeffery; Belcher, Angela M; Naumov, Anton V
Abstract: Near-infrared (NIR) emissive nanomaterials are desired for bioimaging and drug delivery applications due to the high tissue penetration depth of NIR light, enabling in vitro / ex vivo / in vivo fluorescence tracking. Considering the scarcity of NIR-fluorescing biocompatible nanostructures, we have for the first-time synthesized nanometer-sized reduced graphene oxide-derived graphene quantum dots (RGQDs) with NIR (950 nm) emission highly biocompatible in vitro with no preliminary toxic response in vivo. RGQDs are obtained in a high-yield (∼90%) top-down sodium hypochlorite/ultraviolet-driven synthetic process from non-emissive micron-sized reduced graphene oxide (RGO) flakes. This oxidation of RGO yields quantum dots with an average size of 3.54 ± 0.05 nm and a highly crystalline graphitic lattice structure with distinguishable lattice fringes. RGQDs exhibit excitation-independent emission in the visible and NIR-I region with a maximum NIR quantum yield of ∼7%. Unlike their parent material, RGQDs show substantial biocompatibility with ∼75%–80% cell viability up to high (1 mg ml −1 ) concentrations verified via both MTT and luminescence-based cytotoxicity assays. Tracked in vitro via their NIR fluorescence, RGQDs exhibit efficient internalization in HeLa cells maximized at 12 h with further anticipated excretion. In vivo, RGQDs introduced intravenously to NCr nude mice allow for fluorescence imaging in live sedated animals without the need in sacrificing those at imaging time points. Their distribution in spleen, kidneys, liver, and intestine assessed from NIR fluorescence in live mice, is further confirmed by excised organ analysis and microscopy of organ tissue slices. This outlines the potential of novel RGQDs as NIR imaging probes suitable for tracking therapeutic delivery in live animal models. A combination of smaller size, water-solubility, bright NIR emission, simple/scalable synthesis, and high biocompatibility gives RGQDs a critical advantage over a number of existing nanomaterials-based imaging platforms.